Performance Study of NiO-TiO₂-CuO Nanocomposite Supported by Reduced Graphene Oxide as an Anode Candidate for Lithium-Ion Battery Development - Muh Edihar; Kaharuddin Kaharuddin; Maulidiyah Maulidiyah; Thamrin Azis; Mawaddah Zaqinah Diah; Muhammad Nurdin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
In an effort to enhance the performance of lithium-ion batteries (LIBs), this study developed a NiO-TiO2-CuO nanocomposite supported by reduced graphene oxide (rGO) as an anode material. The nanocomposite was synthesized via a hydrothermal method and characterized using FTIR, XRD, and SEM-EDX techniques to understand its structure and material properties. The FTIR spectrum confirmed the presence of C=C bonds (1612-1512 cm-1) and C–O bonds (1147-1099 cm-1) from rGO, as well as Ni-O (408 cm-1), Cu-O (669 cm-1), and Ti-O (549 cm-1). The XRD patterns revealed the crystalline phases of NiO at 2θ = 37° (111), 43° (200), and 62.8° (200); TiO2 at 2θ = 25.3° (101), 48° (101), and 55° (211); and Cu-O at 2θ = 35.6° (111) and 39.8° (022). SEM-EDX images showed small aggregated particles forming a relatively uneven surface with spherical morphology, with an average particle size of 33.25 nm. Electrochemical testing using cyclic voltammetry (CV) demonstrated that the material exhibited a stable specific capacity (Csp) of 6.3 mAh/g after five cycles at a scan rate of 1 V/s. Additionally, the specific capacity significantly increased to 44.15 mAh/g at a scan rate of 0.05 V/s, indicating excellent electrochemical performance. These results suggest that the NiO-TiO2-CuO/rGO nanocomposite has potential as an efficient anode material for lithium-ion battery applications, offering good cycle stability and enhanced energy storage capacity.